Myths of love exploring myth-making through a thematic analysis of Filipina-White man couple vlogs - Albao, Maria Angelia
This paper investigates how Filipina-white man couples use Youtube vlogs in constructing, perpetuating, or subverting cultural myths about interracial relationships. Through Roland Barthes' work Mythologies (1972), the study examined how vlogs function as cultural texts that naturalize or contest dominant ideologies created by histories of colonialism and socio-economic narratives. The study specifically explored how Filipina-white man couples, through their vlogs, either construct, convey, perpetuate, or challenge myths around interracial relationships. Barthes's framework of denotation, connotation, and myth was complemented by Pierre Bourdieu's reflexivity (1989), which places the researcher's lived experience as a Filipino in an interracial relationship as integral to the analysis. Through its narrative aspects, this research explored how vlogs interact with myths like the "sagot sa kahirapan”, “gold digger Filipina”, “caused by colonial mentality”, “nanalo sa jackpot”, “sexualized, seductress Filipina”, and “perfect wife Filipina”. The findings highlight that vlogs have a potential dual role: to directly or indirectly respond to the myths or create emerging narratives. This study contributes to media and cultural studies by showing the evolving role of digital platforms in the formation of contemporary cultural discourses.